1989
DOI: 10.1002/j.2048-7940.1989.tb00667.x
|View full text |Cite
|
Sign up to set email alerts
|

Falls in the Rehabilitation Setting: Incidence and Characteristics

Abstract: A prospective six-month study was conducted to determine a high-risk index for medical rehabilitation patients who fall. Variables studied for all patients included demographics, medical conditions, associated symptoms, orthostatic blood pressure measurements, physical function, posture control, proprioception, use of physical restraints, and medications, A detailed examination of the fall events was also conducted. Of the 143 patients studied, 46 (32%) fell at least once, making a total of 84 falls. Impaired … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
1
2

Year Published

1992
1992
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(41 citation statements)
references
References 27 publications
1
36
1
2
Order By: Relevance
“…wandering, agitation) have been linked to increased falls in this population (Kiely et al, 1998;Marx et al, 1990;Mion et al, 1989). Falls can have serious consequences for the elderly patient, including bone fractures and subsequent death or discharge to a nursing home (Fuller, 2000).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…wandering, agitation) have been linked to increased falls in this population (Kiely et al, 1998;Marx et al, 1990;Mion et al, 1989). Falls can have serious consequences for the elderly patient, including bone fractures and subsequent death or discharge to a nursing home (Fuller, 2000).…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, sleep disruptions and reduced functional abilities of the patient have been associated with nursing home placement (Chenier, 1997). Night-time wandering is not uncommon in this population (Kiely et al, 1998;Mion et al, 1989), putting patients at risk of getting lost or falling, which may result in fractures or other injuries (Klein et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Falls are a common occurrence among elderly inpatients in subacute hospitals and are generally reported to affect between 13% and 32% of admitted patients 1 2. In stroke rehabilitation units, falls have been reported in up to 47% of patients 3.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, impaired proprioception could be a contributing factor to falls. Mion et al [42] identified impaired proprioception as a contributing factor to falls among patients in a rehabilitative setting. Moreover, Camicioli et al [13] showed that the disruption of proprioceptive input was the most important determinant of quantitative balance performance in subjects older than 80 years.…”
Section: Introductionmentioning
confidence: 99%